Undergraduate medical students’ perception regarding computer assisted learning in experimental pharmacology practical - Kumar, Manish; Kumar, Manish; Mishra, Hitesh; Manjhi, Pramod Kumar; Chandra, Akash; Mohan, Lalit; Dikshit, Harihar (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Main objective of this study was to find out the students’ perception and to obtain feedback towards the use of Animal Simulator to demonstrate drug effects in terms of its acceptability, advantages and disadvantages of Computer Assisted Learning (CAL) in experimental pharmacology practical as an educational tool. Methods: Questionnaire based study, done on randomly and voluntarily selected ninety-six fourth and fifth semester MBBS Students. Divided into four groups and each group contained 24 students. Students were taught experimental pharmacology practical online using Animal simulator (CAL- Computer Assisted Learning) for 2 hours on different days in three sessions. Questions and their feedback was taken during these sessions and presented in tables. Statistical analysis of data was done using Graph Pad software. Results: Majority of students i.e. 64 (66.67%) agreed that in vitro and in vivo experiments on animals are essential for better understanding and learning of the biological process. Students were agreed to the majority of the statements for CAL like enjoyable and time saving, easy to perform, contributes more to understanding theoretical concepts, no experimental error seen, welcome change and best alternative to laboratory practical and many experiments can be demonstrated in a short time. Students were disagreed on statements like CAL is an effective method of teaching practical aspects and preferred experimentation than laboratory practical. Majority of students given yes/positive response to questions showing advantages of using CAL. Also, positive feedback was obtained regarding questions showing disadvantages of using CAL software. Conclusions: Students’ perception regarding practical with CAL laboratory using animal simulator was good. The overall view was expressed that they found the exercises interesting and educationally beneficial. Computer assisted learning is a feasible and very effective teaching and learning method in pharmacology with huge potential to change the way of learning as it meets the majority of the learning objectives.